MOBILIZATION OF THE CIRCASSIANS IN VIEW OF THE 2014 OLYMPIC GAMES - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2012)
When in Europe, I am often asked about my occupation at home. My answer, “I study the ethnography of the peoples of the Northern Caucasus,” baffles people; most of them do not know where to look for the Caucasus on the map, however everyone recognizes the word “Chechens,” an echo of the Chechen wars of the 1990s. At the turn of the 2010s, the world learned about another North Caucasian ethnicity, known abroad as the Circassians, the new ethnic name came with the decision of the IOC to organize the 2014 Winter Olympic Games in Sochi, the historical home of the Adighe peoples. Who are the Adighes or Circassians? The latter term was used by the first European travelers who reached the Caucasus several centuries ago. Ethnographers use the blanket term “Adighes” to refer to several kindred ethnic sub-groups and sub-ethnicities who speak the Adighe languages. They are the Kabardins, who live in Kab-ardino-Balkaria; the Circassians, who live in Karachay-Cherkessia; and the Western Adigh-es (known in Soviet times as the Adighes from the name of their autonomous region called Adi-gey). The Adighes are divided into smaller ethnic groups—Shapsugs, Natukhays, Abadzekhs, Temirgoys, Bjedugs, etc. Some of the Western Adighes live along the Black Sea coast, in the Lazarevskoe and Tuapse districts of the Kras-nodar Territory, between the cities of Sochi and Tuapse.